İş sağlığı ve güvenliği hukuku: inşaat sektöründe uygulama sorunları - Pınar, Esin (My University, 2013)
İŞ SAĞLIĞI VE GÜVENLİĞİ, Bugün dünyada ve ülkemizde önemi daha iyi anlaşılan ve yoğun çalışmalar yapılan konu haline gelmiştir. ILO 155 ve 161 Sayılı Sözleşmelerinin dayatması ve AB mevzuatına uyum sürecinin parçası olarak 20.06.2012 tarihinde yasa koyucu tarafından 6331 sayılı İş Sağlığı ve Güvenliği Yasası kabul edilmiştir. 6331 sayılı yasada yasanın kapsamı ve amaçları belirtildikten sonra, tanımlara, işverenin iş sağlığı ve güvenliği hukukunda doğan yükümlülüklerine, çalışanların hak ve sorumluluklarına ve iş sağlığı ve güvenliği teftişine dair düzenlemelere yer verilmiştir. Hızla kabul edilen bu yasanın uygulamadaki sorunlarını giderme konusunda yeterliliği tartışmalıdır. Tez kapsamında, Yasanın yeterliliği konusunu tartmak amacıyla inşaat sektöründeki çalışma ilişkilerinin taraflarıyla görüşmeler yapılmıştır. Araştırma çalışma yaşamına ilişkin eksiklerin tespit edilmesi ve iş kazası/ meslek hastalılarının en aza indirilebilmesi için iş sağlığı ve güvenliği mevzuatında yapılması gerekenlere dair tartışmalara katkı sunmayı amaçlamaktadır. Sayılı Yasa, İş Sağlığı ve Güvenliği Yasası, 155 ve 161 sayılı ILO Sözleşmeleri, İnşaat Sektörü Çalışma İlişkileri, AB Müktesebatı.

Occupational Health And Safety/ Security is a significant issue at the national and the global scale and there are lots of prominent studies given regarding the issue. In Turkey, as a part of the integration to EU Acquis Communautaire and due to impositions of ILO Convention No. 155 and 161 Law of Occupational Health and Safety numbered 6331 is adopted in 20.06.2012. The law states the scope and objectives of the legal regulation and gives place to the responsibilities of the employer arising from Occupational Health and Safety/ Security law and to the right and duties of the employee and also to the regulations regarding the control of safety and health at work. This law, which is adopted urgently, is not sufficient enough to meet the needs and to overcome the problems of the implementation of laws. In this research, the competence of the law will be discussed with a specific reference to its implementations in the construction sector. In accordance with this objective, interviews and questionnaires are carried with the parts of the employment relations in the construction sector. Based on this field research, this study aims to make contributions to the discussions on the legal regulations regarding occupational health and security that could reduce the work accident and occupational illnesses. With this point of view, it is important to determine the shortcomings of the occupational health and security literature that has an interdisciplinary character and pave the way for new discussions. Law numbered 6331, Occupational Health and Safety, ILO Convention No. 155 and no.161, Labour Relations in the Construction Sector, EU Acquis Communautaire
Keywords: Endüstriyel İlişkiler; İş Güvenliği; İş Sağlığı